2007
DOI: 10.2136/sssaj2005.0324
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Effects of Soil Properties on Phosphorus Retention Capacity

Abstract: Phosphorus retention ability of soil has been predicted from different combinations of soil properties as a result of significant correlations between these variables. However, a significant correlation between P retention capacity and a soil property does not necessarily imply a significant direct effect of the soil property on P retention. The objective of this study was, therefore, to evaluate the direct and indirect influence of soil properties on P retention capacity of neutral to calcareous soils of Mani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
37
1
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 25 publications
5
37
1
6
Order By: Relevance
“…3d). The inclusion of ammonium oxalate Al (Al Ox ) into the regression equations as suggested by Ige et al (2007) improved both the slope and the coefficient of determination for P 150 and S max , thus improving the overall prediction of the retention capacity of these soils (Fig. 2e and 3e).…”
Section: Independent Assessment Of P Retention Capacity Equations Formentioning
confidence: 99%
See 1 more Smart Citation
“…3d). The inclusion of ammonium oxalate Al (Al Ox ) into the regression equations as suggested by Ige et al (2007) improved both the slope and the coefficient of determination for P 150 and S max , thus improving the overall prediction of the retention capacity of these soils (Fig. 2e and 3e).…”
Section: Independent Assessment Of P Retention Capacity Equations Formentioning
confidence: 99%
“…Ige et al (2003) predicted PRC of Nigerian tropical soils from ammonium oxalate extractable Al, soil pH and the percent clay content. For Manitoba soils, Ige et al (2007) suggested Mehlich-3 extractable Ca and Mg and ammonium oxalate extractable Al as the best variables for PRC estimation. Brock et al (2007), working with manure-amended soils, predicted PRC from Mehlich-3 extractable Al, Fe and Ca.…”
mentioning
confidence: 99%
“…There are significant correlations between soil pH and exchangeable Ca (r=0.734), soil pH and exchangeable Mg (r=0.676) and Soil pH and clay percentage (r=0.623). Significant positive correlations with soil exchangeable Ca, exchangeable Mg and soil clay content with soil pH have been found by Ige et al [2]. Soil available phosphorus showed a significant negative relationship with soil clay percentage (r=-0.329) at 0.01 probability level.…”
Section: Citationmentioning
confidence: 58%
“…2 (a) and 2 (b) and be described in the equation of y= -7.4987x+716.65 (after one month) and y= -1.0021x+103.24 (after four months). The negative notation in the equation showed the inverse correlation between the P-retention and available P. In this case, the decreasing of Pretention is followed by the increasing of available P. Besides the correlation with available P, the value of Pretention can have correlation to many soil characteristics like exchangeable Ca, Mg and Al as investigated and stated by [16].…”
Section: Available Pmentioning
confidence: 75%